Effects of Superficial Keratectomy in Peripheral Hypertrophic Subepithelial Corneal Opacification on Front and Back Corneal Astigmatism: - Corneal surface analysis in PHSCO after superficial keratectomy -. (4th March 2021) - Riedl, Jana C; Schuster, Alexander K; Musayeva, Aytan; Wasielica-Poslednik, Joanna; Marx-Gross, Susanne; Gericke, Adrian
ABSTRACT: Purpose: To evaluate changes of anterior and posterior corneal astigmatism after superficial keratectomy in peripheral hypertrophic subepithelial corneal opacification (PHSCO). Methods: Patients with PHSCO, who had received superficial keratectomy with mitomycin C 0.02%, were included in this retrospective study. Scheimpflug imaging of the cornea (Pentacam®, Oculus, Wetzlar, Germany), best-corrected visual acuity (BCVA) and objective refraction were determined preoperatively and 3 months after superficial keratectomy. Results: Fifteen eyes of 15 patients (age: 55 ± 16 years; range: 36–82 years) were included. The mean preoperative BCVA was logMAR 0.4 ± 0.2 and improved to logMAR 0.21 ± 0.3 ( p < .01) postoperatively. The median preoperative astigmatism of the anterior corneal surface was 4.67 ± 2.4 D (range: 0.9–13.2 D) and decreased to 1.4 ± 0.4 D (range: 0.8–2.3 D) 3 months after surgery. The median astigmatism of the posterior corneal surface was 0.6 ± 0.5 D (range: 0.1–2.2 D) before surgery and decreased to 0.3 ± 0.2 D (range: 0–0.7 D) 3 months after surgery. Conclusion: Superficial keratectomy reduces anterior corneal astigmatism more than posterior corneal astigmatism in patients with PHSCO. Furthermore, a myopic shift and corneal steepening in the peripheral and mid-peripheral cornea was observed after removal of the subepithelial corneal opacification spots.